Association of tumour necrosis factor‐α polymorphism in patients with end stage renal disease. (June 2015) - Singh, Kamini; Prasad, Kashi Nath; Mishra, Priyanka; Singh, Satyendra Kumar; Kharwar, Nagendra Kumar; Prasad, Narayan; Gupta, Amit; Srivastava, Janmejai Kumar
Abstract: Aim: Cytokines play a critical role in the pathophysiology of end stage renal disease (ESRD). Tumour necrosis factor‐a (TNF‐α) is an important cytokine involved in initiation and progression of renal diseases. The present study evaluated the association of specific alleles/genotype of TNF‐α with chronic renal failure (CRF) and ESRD. Methods: A total of 30 CRF patients who were not on renal replacement therapy, 85 ESRD patients and 120 healthy controls were included in the study. The ESRD patients belonged to two subgroups: patients on peritoneal dialysis (PD) without peritonitis ( n =  50) and with peritonitis ( n =  35). TNF‐α genotype (‐308 G > A) was determined by polymerase chain reaction‐restriction fragment length polymorphism. Level of TNF‐α was detected in the sera of patients and healthy controls by enzyme linked immunosorbent assay (ELISA), and also in the dialysate of patients on PD. Results: The genotypic distributions of TNF‐α (‐308 G > A) were significantly different between patients and controls. Homozygous A/A genotype had significant association with CRF and ESRD ( P  < 0.001, odds ratio [OR] = 25.02). Frequency of homozygous A/A genotype was significantly higher in all subgroups of patients than controls (CRF 40% vs control 2.5%, P  = 0.001; PD 54% vs control 2.5%, P  < 0.001 and PD with peritonitis 62.8% vs control 2.5%, P  < 0.001). Patients with homozygous A/A genotype had significantly elevated levels of TNF‐α in the sera of patients and in the dialysate of PD patients. Conclusions: Individuals with homozygous TNF‐α (‐308 G > A) polymorphisms has significant association with CRF and ESRD, and thus may be a predictor for development of the disease. Elevated TNF‐α may be a contributory factor. Summary at a Glance: Individuals with homozygous TNF‐α (−308G>A) polymorphisms appear to have a significant association with CRF and ESRD, and thus this may be a predictor for development of the disease. These patients also demonstrated elevated serum TNF‐α levels, which may be a contributory factor.